ОРОЛБЎЙИ МИНТАҚАСИДА ЖОЙЛАШГАН МАКТАБ ЎҚУВЧИЛАРИДА “Z-SCORE”-ТАҲЛИЛ ВА ПЕРЦЕНТИЛЬ ҚИЙМАТЛАРИ БЎЙИЧА ЖИСМОНИЙ РИВОЖЛАНИШ ДАРАЖАСИ ТАҲЛИЛИ - Утемуратов, Н.А.; Хушматов, Ш.С. (SCIENCE and SOCIETY, 2023)
In the study, a Z-score analysis and analysis of the percentile values of the average values were carried out anthropometric indicators for students of schools No. 2 and No. 3 (7-11 years old) located in the Moinak district of the Aral Bay. regions of the Republic of Karakalpakstan were taken into account on the basis of distribution analysis.